(untitled) (REMUNOM, 2025)
This research aims to describe the integration of logistics processes with the service operations of a domestic laundry that operates in the city of Manaus. The methodology was a case study, whose data were collected through three sources of evidence (interview, observation and survey), to understand the business model implemented, the steps of the operations process used, the logistics procedures executed and the level of customer satisfaction, with the results generated from content analysis (interview and observation) and descriptive statistics (survey). The results showed that a) the business model is small, focused on individuals, with low operating costs and initial capital, b) the operations process is carried out in seven steps (collection, transfer, washing, drying, ironing, packaging and delivery), with some bottlenecks that can be solved with the acquisition of a specialized machine, c) the service logistics presents challenges in routing, scheduling and increasing customer satisfaction and d) customer satisfaction can be considered high, but can be improved. The conclusion reveals that the organization’s logistics processes are integrated with its service operations; however, it is possible that this integration can be further enhanced by addressing the operational and logistics bottlenecks encountered.